PARTICIPATION IN PHYSICAL ACTIVITIES AND EVERYDAY LIFE OF PEOPLE WITH DISABILITIES - Merete Kissow, Anne; Singhammer, John (European Journal of Adapted Physical Activity, 2012)
The purpose of this study was to investigate the correlation between participating in physical activity on a regular basis and civic activities for people with disabilities. Data were collected using telephone interviews with 1,321 people, who reported having some impairment related to legs, arms, hands, vision, behaviour or intellect. The sample was randomly selected by The Danish National Centre for Social Research, which also conducted the interviews. The data material is representative of all persons in Denmark aged 16 - 64 years according to gender, age, income, employment and education, and analyses were conducted using STATA 11.2. The study observed a significant correlation between a participation in physical activities and employment, educational status, volunteerism, leisure time schooling and membership in a disability organization. Among the participants in physical activities, women were in the majority, and a correspondence analysis revealed complex relations between participation in physical activities and civic activities, which might be elaborated on through further research. The results of this study give supporting arguments and provide the impetus for including physical activity and sport as a consistent means in the rehabilitation process, while improving the opportunities for people with disabilities to help gain access to appropriate physical activities in their local community.
Keywords: Physical activities; civic activities; correspondence analysis